Percutaneous CT‐Guided Cryovagotomy in Patients with Class I or Class II Obesity: A Pilot Trial. Issue 8 (24th July 2019) - Prologo, J. David; Lin, Edward; Horesh Bergquist, Sharon; Knight, Jackie; Matta, Hazem; Brummer, Marjin; Singh, Arvinpal; Patel, Yogi; Corn, David
Abstract : Objective: This study evaluated the safety of percutaneous CT‐guided cryoablation of the vagus nerve (percutaneous cryovagotomy) in participants with class I or class II obesity. Methods: The study was an open‐label, single‐group, prospective pilot investigation designed around safety‐related stopping criteria. Twenty participants with 30 > BMI > 37 underwent percutaneous cryovagotomy with follow‐up visits at day 7, 45, 90, and 180. Data related to adverse events, technical success, weight loss, quality of life, dietary intake, global impressions of hunger change, activity, and body composition were analyzed. Results: The procedural technical success rate was 100%. There were no adverse events in 19 participants who completed the trial. Ninety‐five percent of patients reported decreased appetite following the procedure, and reductions in mean absolute weight and BMI were observed at all time points. The mean quality of life and activity scores improved from baseline to 6 months post procedure, and mean caloric intake and overall body fat decreased over the same period. Conclusions: Percutaneous CT‐guided cryovagotomy is feasible and was tolerated without complications or adverse events in this cohort. Quantitative preliminary data from this pilot investigation inform the design of a larger prospective randomized clinical trial.